Improved Tracking Accuracy of Par-4 Delta Parallel Robot Using Optimized FOPID Control with PSO Technique - Mahdi, Shaymaa M.; Abdulkareem, Ahmed I.; Humaidi, Amjad J. (Universitas Muhammadiyah Yogyakarta, 2025)
The Par-4 Delta parallel robot is an excellent choice for most pick-and-place applications. The parallel robot has complex and high nonlinearities and the choice of control design is one key to improving the tracking performance and accuracy of parallel robots. This study proposes two structures of proportional-derivative-integral (PID) controller. The first scheme utilized Integer-order setting of controller's terms, while the second structure used integral and derivative terms with fractional orders and it is termed as fractional-order PID (FOPID) controller. The terms of FOPID controller are synthesized based on fractional calculus theorem. It has been shown that FOPID controller has high efficacy when applied to complex and nonlinear systems. However, the tuning of its terms is a critical issue in its design. As such, an algorithm-based particle swarm optimization (PSO) has been developed to tune the parameters of FOPID controller such as to achieve global minimum of tracking errors Par-4 Delta parallel robot. The effectiveness of optimized FOPID controller has been verified via numerical simulation and it is compared to integer PID (IPID) controller with the same PSO algorithm. The computer simulations have showed that better tracking errors have been obtained with FOPID controller compared to its counterpart. Using the root mean square of error (RMSE) as the metric of evaluation, the numerical results showed that PSO-FOPID achieved 60% and 62.9% improvement in terms of tracking accuracy along both the x-axis and the z-axis, respectively, as compared to IOPID applied controller techniques.